Reconstruction and characterization of full-length begomovirus and alphasatellite genomes infecting pepper through metagenomics - Bornancini, Veronica Andrea (2020)
In northwestern Argentina (NWA), pepper crops are threatened by the emergence of begomoviruses due to the spread of its vector, Bemisia tabaci (Gennadius). The genus Begomovirus includes pathogens that can have a monopartite or bipartite genome and are occasionally associated with sub-viral particles called satellites. This study characterized the diversity of begomovirus and alphasatellite species infecting pepper in NWA using a metagenomic approach. Using RCA-NGS (rolling circle amplification-next generation sequencing), 19 full-length begomovirus genomes (DNA-A and DNA-B) and one alphasatellite were assembled. This ecogenomic approach revealed six begomoviruses in single infections: soybean blistering mosaic virus (SbBMV), tomato yellow spot virus (ToYSV), tomato yellow vein streak virus (ToYVSV), tomato dwarf leaf virus (ToDfLV), sida golden mosaic Brazil virus (SiGMBRV), and a new proposed species, named pepper blistering leaf virus (PepBLV). SbBMV was the most frequently detected species, followed by ToYSV. Moreover, a new alphasatellite associated with ToYSV, named tomato yellow spot alphasatellite 2 (ToYSA-2), was reported for the first time in Argentina. For the Americas, this was the first report of an alphasatellite found in a crop (pepper) and in a weed (Leonurus japonicus). We also detected intra-species and inter-species recombination